Influence of CYP2D6, CYP3A4 and CYP2C19 Genotypes on Recurrence of Plasmodium vivax - Cardoso, Jaiana L. M.; Salazar, Yanka E. A. R.; Almeida, Anne C. G.; Barbosa, Laila R. A.; Silva, Emanuelle L.; Rodrigues, Maria Gabriela Almeida; Rodrigues-Soares, Fernanda; Sampaio, Vanderson S.; Siqueira, André M.; Lacerda, Marcus V. G.; Monteiro, Wuelton M.; Melo, Gisely C. (Frontiers in Tropical Diseases, 2022)
Background The influence of the CYPs (cytochrome P-450) in the success of antimalarial therapy remains uncertain. In this study, the association of CYP2D6, CYP2C19 and CYP3A4 polymorphisms and predicted phenotypes with malaria recurrence was investigated. Methods After diagnosis of vivax malaria, individuals treated at a reference center in Manaus were followed up for 180 days. Patients were separated into two groups: a recurrence group and a non-recurrence group. Genotyping of CYP2D6, CYP2C19 and CYP3A4 was performed using a TaqMan™ assay and real-time PCR. Findings The frequencies of decreased-function and normal-function alleles and phenotypes for all CYPs were similar between the groups, except for the CYP2D6*2xN allele (p=0.047) and the CYP2D6 gUM phenotype (p=0.057), which were more frequent in individuals without recurrence. Despite this, the CYP2D6, CYP2C19 and CYP3A4 genotypes had no association with an increased risk of recurrence. CYPs polymorphisms also had no influence in parasite clearance, neither in the time nor the number of recurrence episodes. MAIN Conclusion This prospective cohort study demonstrated that CYP2D6, CYP2C19 and CYP3A4 polymorphisms have no influence on malaria recurrence. Nonetheless, our findings suggest that the CYP2D6 predicted ultrarapid phenotype was less susceptible to recurrence, and that patients with the CYP2D6 gUM phenotype are less susceptible to primaquine failure. Additional investigation of pharmacogenetics and pharmacokinetics are needed before implementing CYP analysis to better orientate individualized radical treatment of vivax malaria in reference centers that treat patients with multiple recurrences.